Influence of finite deformations on the growth mechanism of microvoids contained in structural metals - Dornowski, W. (Archives of Mechanics, 1999)
In this paper an analysis of the growth mechanism of the single microvoid for finite deformations is presented. A hollow sphere model is assumed. Such a model has been considered in many previous papers, however on the assumption that the strains remain small. The material surrounding the microvoid is assumed to be work-hardening, viscoplastic, described by the constitutive equations formulated by Perzyna [1]. Quantitative and qualitative distinctions between the presented solution and geometrically linear solution are discussed. On the basis of the obtained solution, constitutive functions of a certain damage evolution equation for the complex stress state have been identified. A numerical example of the fracture analysis for a structural element is presented.